New immunosuppressive drugs in heart transplantation - Costanzo, Maria Rosa (BioMed Central, 2001)
Only a few randomized clinical trials have been performed so far in heart transplant recipients, mainly because of the relatively small number of heart transplants performed worldwide each year. The main focus of the few controlled trials that have been completed has been the prevention and treatment of heart allograft rejection. In the area of pharmacologic immunosuppression, both biological agents and drugs have been the subject of investigation. Among the biological agents, chimeric monoclonal antibodies directed against the interleukin (IL)-2 receptor, which have been found to be safe and effective in renal transplant recipients, are now undergoing the test of controlled trials in heart transplant recipients. Immunosuppressive drugs that have been studied in controlled trials include calcineurin inhibitors (such as the microemulsion formulation of cyclosporine and tacrolimus) and inhibitors of purine synthesis, such as mycophenolate mofetil. Non-pharmacologic prophylactic immunosuppression with photopheresis has also been tested in a prospective, multicenter, randomized trial. New immunosuppressive regimens, such as mycophenolate mofetil combined with a monoclonal antibody against the IL-2 receptor, are being tested with the aim to reduce or eliminate calcineurin inhibitors or corticosteroids. Although clinical approaches to the induction of tolerance have undergone preliminary clinical evaluation, the ability to induce tolerance to an allograft in humans remains an elusive goal.